STRATEGI PEMASARAN PRODUK TABUNGAN HAJI PADA BANK SYARIAH INDONESIA KCP JAMBI SIPIN BAKARUDDIN - Silvia Dewi Saputri; Ahmad Syahrizal; Nurrahma Sari Putri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
A marketing strategy is a set of goals and objectives, policies and rules that give direction to marketing efforts over time, providing direction to marketing efforts at every level and location. Marketing is a concept that uses many philosophies in its application. The marketing concept can be realized by identifying and formulating consumer wants and needs and must create products, prices, promotions, distribution that suit the conditions of target consumers. This research uses qualitative methods and also uses data collection techniques through interviews. The data used is primary data, namely data taken directly from the research site. The results of this research show that the marketing strategy for Hajj savings products implemented by Bank Syariah Indonesia KCP Jambi Sipin Bakaruddin is in the form of a 7P marketing mix which includes product, price, place, promotion, people, physical evidence and process strategies with several obstacles for Bank Syariah Indonesia in marketing Hajj savings products. The input for Bank Syariah Indonesia KCP Jambi Sipin Bakaruddin is that the bank should evaluate each marketing strategy for Hajj savings products that has been implemented and then strategies that have deficiencies can be corrected and perfected again.